Computational methods in systems biology : 14th International Conference, CMSB 2016, Cambridge, UK, September 21-23, 2016, Proceedings /: 14th International Conference, CMSB 2016, Cambridge, UK, September 21-23, 2016, Proceedings. (2016) - Unknown
No abstract available